Syncretism of Body and Sexuality in The Catcher in the Rye - Thapa, Hukum (Humanities and Social Sciences Journal, 2022)
The present paper examines the syncretism of body and sexuality and its consequences in The Catcher in the Rye written by J.D. Salinger. This paper further discusses how the young adult Holden Caulfield perceives his body and sexuality; and how the body and sexuality work in The Catcher in the Rye. Moreover, this paper analyzes body celebration, abuse and sexuality of young adult Holden. This study argues that young adults perceive their body as a means of power, freedom, identity and maturity. Young adults employ their body and sexuality as agencies to be distinct and noticeable in their community and society. For these purposes, this paper primarily employs the ideas of Roberta S. Trites and Judith Butler as theoretical tools. This paper opens an avenue for further research about young adults of Nepal and other topography besides America.